2011
DOI: 10.1007/s12665-011-0959-2
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater flow system in Bengal Delta, Bangladesh revealed by environmental isotopes

Abstract: A total number of 328 groundwater samples are analysed to evaluate the groundwater flow systems in Bengal Delta aquifers, Bangladesh using environmental isotope ( 2 H, 18 O, 13 C, 3 H, and 14 C) techniques. A welldefined Local Meteoric Water Line (LMWL) d 2 H = 7.7 d 18 O ? 10.7 % is constructed applying linear correlation analyses to the monthly weighted rainfall isotopic compositions (d 18 O and d 2 H). The d 18 O and d 2 H concentrations of all groundwater samples in the study area are plotted more or less … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 17 publications
(13 reference statements)
1
22
0
Order By: Relevance
“…The earliest Ganges delta development phase took place about 5-2.5 Ka (Allison et al 2003). Majumder (2008) observed that the age of the deep groundwater fell along the seawater line ranged from nearly *6 to 25 Ka. So it seems that, brackish water originated from the sea is trapped within the aquifer.…”
Section: Hydrogeochemical Process Evaluationmentioning
confidence: 99%
“…The earliest Ganges delta development phase took place about 5-2.5 Ka (Allison et al 2003). Majumder (2008) observed that the age of the deep groundwater fell along the seawater line ranged from nearly *6 to 25 Ka. So it seems that, brackish water originated from the sea is trapped within the aquifer.…”
Section: Hydrogeochemical Process Evaluationmentioning
confidence: 99%
“…Groundwater at 137 mbgl on the northern edge of Dhaka contained 43.7 pMC (percent modern carbon) for dissolved inorganic carbon (Majumder et al 2011), which could indicate anything between modern recharge and an age of 2,500 years, depending on the corrections applied (e.g., Hoque and Burgess 2012) to derive an age from this value. Groundwater ages at two locations within 4 km of the Buriganga River were estimated to ca.…”
Section: Agesmentioning
confidence: 99%
“…Bangladesh has abundant, easily accessible groundwater within the unconsolidated, fluvio-deltaic sands that provide drinking water (Majumder et al, 2011) for 97% of its 160 million inhabitants (BBS, 2014). The most easily accessible shallow groundwater <100 m deep often contains toxic levels of arsenic (As) (DPHE/BGS 2001), although its distribution is highly heterogeneous (van Geen et al, 2003).…”
Section: Introductionmentioning
confidence: 99%